Soil-site Characteristics and Productivity Assessment of Nara-Dada-Manjhi Watershed in Semi-arid Hilly Tract of Punjab - Sharma, K R; Jassal, H S; Sondhi, A (Annals of Arid Zone, 2016)
The soil-site characteristics of Nara-Dada-Manjhi watershed, situated on the southern slopes of the Shiwalik hills in Hoshiarpur district of Punjab, were studied to work out the land productivity rating. Based on inherent soil characteristics and externaJ land features, the Storie Index Rating factors A, B, C and X were evaluated. The results reveal that the soils of Nara-Dada-Manjhi watershed belong to four land productivity grades. The soils of lower piedmont plains generally belong to grade 2 and are suitable for most crops with good yield potential, whereas soils from upper piedmont plains qualify for grade 3 and may be used for selected crops. The soils developed on choe beds and hills qualify for grades 5 and 6, respectively. The soils on choe beds have limited use, except for pasture, whereas soils on hills are not suitable for agriculture.